Trading forest products in South-Eastern Zimbabwe: ecology, economics and politics of woodcarving - Standa-Gunda, W.; Braedt, O. (Center for International Forestry Research, 2004)
The commercial use of natural resources to manufacture products for sale to tourists has become a significant supplementary source of income to rural people in all areas of Zimbabwe. The use of natural resources to produce woodcarving has been controversial because of the volume of woods used and the impact on woodlands. This article explores some of the baseline data, which have been gathered under an economic study of the woodcarving industry along the Masvingo-Beitbridge road. Results of the analysis show that returns to time invested in carving are higher than from other locally available alternatives. The growth of the industry is primarily attributed to (a) the drought years, which forced people to seek alternative livelihood options; (b) the economic structural adjustment programme that devaluate the Zimbabwean dollar thereby attracting more foreign visitors while at the same time resulting in loss of jobs especially in the public sectors as subsidies were removed; (c) the collapse of apartheid in South Africa and the several years of domestic political stability in Zimbabwe, which led to a significant increase in tourist traffic between the two countries. The implications of the results are considered with respect to the sustainability of this growing sector.